Izražanje jeze in sovraštva na spletu - Erzar, Tomaž (Bogoslovni vestnik, 2024)
The paper analyses the phenomenon of online hate speech in terms of the emotions involved and describes the consequences of putting displaced anger, rage, hate, and frustration onto social network users. It analyses the psychosocial motivations of the perpetrators and demonstrates that, while the online media satisfy their need for visibility, approval, and belonging, they also enclose them in an impersonal, virtual space of artificial connectedness that lacks the key features of interpersonal connectedness in the real world. Because they are mostly acting as angry, offended victims, the users of contemptuous and hateful online speech cannot achieve the public persuasiveness and authenticity that only expressions of vulnerability can provide. In this respect, the reach of angry speech on social networks appears to be smaller than its resonance would suggest.
Keywords: affiliation; authenticity; displaced anger; družbena omrežja; hate; hate speech; mladi; need for recognition; nefunkcionalna jeza; potreba po prepoznanju; povezanost; pristnost; social media; sovraštvo; sovražni govor; victim role; vloga žrtve; women; youth; ženske